The Turn of the Screw - James, Henry (Italie ELI, 2010)
A young woman starts her first job as a governess in charge of two young orphans, Miles and Flora, at a country house called Bly. The children are beautiful and well-behaved, but are they too good to be true? When the governess starts to experience strange visions, she suspects that the children are hiding a terrible secret. Are there ghosts at Bly, or is the governess going mad?
Eli Readers is a beautifully-illustrated series of timeless classics and specially-Written stories for learners of English.
Contents, Test, Glossary, Comprehension activities.
Keywords: Ghost story; Reading books; Upper-intermediate level; Language Learning